Age-related accrual of methylomic variability is linked to fundamental ageing mechanisms. Issue 1 (December 2016) - Slieker, Roderick; van Iterson, Maarten; Luijk, René; Beekman, Marian; Zhernakova, Daria; Moed, Matthijs; Mei, Hailiang; van Galen, Michiel; Deelen, Patrick; Bonder, Marc; Zhernakova, Alexandra; Uitterlinden, André; et al.
Abstract Background Epigenetic change is a hallmark of ageing but its link to ageing mechanisms in humans remains poorly understood. While DNA methylation at many CpG sites closely tracks chronological age, DNA methylation changes relevant to biological age are expected to gradually dissociate from chronological age, mirroring the increased heterogeneity in health status at older ages. Results Here, we report on the large-scale identification of 6366 age-related variably methylated positions (aVMPs) identified in 3295 whole blood DNA methylation profiles, 2044 of which have a matching RNA-seq gene expression profile. aVMPs are enriched at polycomb repressed regions and, accordingly, methylation at those positions is associated with the expression of genes encoding components of polycomb repressive complex 2 (PRC2)in trans . Further analysis revealedtrans -associations for 1816 aVMPs with an additional 854 genes. Thesetrans -associated aVMPs are characterized by either an age-related gain of methylation at CpG islands marked by PRC2 or a loss of methylation at enhancers. This distinct pattern extends to other tissues and multiple cancer types. Finally, genes associated with aVMPsin trans whose expression is variably upregulated with age (733 genes) play a key role in DNA repair and apoptosis, whereas downregulated aVMP-associated genes (121 genes) are mapped to defined pathways in cellular metabolism. Conclusions Our results link age-related changes in DNA methylation to fundamental mechanisms that are thought to drive human ageing.